Implementasi Sistem Antrian Online dan On-site di Kelurahan Gebang Putih Surabaya untuk Meningkatkan Efisiensi Layanan Publik - Aziz, Adam Shidqul; Mubtadai, Nur Rosyid; Permatasari, Desy Intan; Saputra, Ferry Astika; Syarif, Iwan; Fariza, Arna; Al Rasyid, M. Udin Harun; Kusuma, Selvia Ferdiana; Sumarsono, Irwan; Ahsan, Ahmad Syauqi; Sa'adah, Umi; Yunanto, Andhik Ampuh; Primajaya, Grezio Arifiyan; Edelani, Renovita; Ramadijanti, Nana; Khoirunnisa, Asy Syaffa; Alfaqih, Wildan Maulana Akbar; Al Falah, Adam Ghazy (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Digitalization is an important step in improving the efficiency of public services, particularly in managing queues in government institutions such as sub-district offices. Kelurahan Gebang Putih Surabaya faces significant challenges in managing its manual queue system, which often results in discomfort for the public due to long waiting times, exceeding 5 minutes. This reduces public satisfaction and causes inefficiencies in the queue process. To address this issue, this study aims to develop and implement a digital queue system that can be accessed both online and on-site, using the User-Centered Design (UCD) approach. This approach ensures that every aspect of the system's design and development focuses on user needs through an iterative process, where the design is adjusted based on direct feedback from users. The proposed solution in this study includes the creation of a mobile and website-based queue system, allowing the public to easily take a queue number online and also enabling quick on-site queueing with a wait time of less than 10 seconds. Another advantage of this system is its automated reporting feature, which facilitates documentation and queue reports, thereby accelerating administration and monitoring to the city government. The results show that the implementation of this system significantly reduces the queue-taking time from over 5 minutes to less than 10 seconds, successfully transforming the manual system into a more efficient digital system, and streamlining the reporting process to the government, which in turn improves the quality and satisfaction of public services.